1992
DOI: 10.1016/0378-1097(92)90159-l
|View full text |Cite
|
Sign up to set email alerts
|

? lectin purified from Vibrio cholerae 01

Abstract: An N-acetyl-D-glucosamine-specific cell associated hemagglutinin (HA) was isolated and purified from a strain of Vibrio cholerae 01 by chitin affinity chromatography followed by separation on Bio Gel P-150. A single stained protein band of 47 kDa in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was observed with the purified HA. HA-antisera produced a single precipitin band against the purified HA in an immunodiffusion test without exhibiting any reactivity towards purified lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The filamentous hemagglutinin of B. pertussis and pertussis toxin contain carbohydrate recognition domains critical for binding to glycoconjugates on cell membranes (41,49). One of the hemagglutinins of V. cholerae has been reported to be specific for N-acetyl-Dglucosamine, the monomeric subunit of chitin, and mediates binding of the bacterial cells to rabbit intestinal epithelial cells (44). Furthermore, it has been shown that Klebsiella pneumoniae is internalized efficiently by cultured human epithelial cells, presumably via an N-glycosylated receptor containing N-acetyl-glucosamine residues (13).…”
Section: Discussionmentioning
confidence: 99%
“…The filamentous hemagglutinin of B. pertussis and pertussis toxin contain carbohydrate recognition domains critical for binding to glycoconjugates on cell membranes (41,49). One of the hemagglutinins of V. cholerae has been reported to be specific for N-acetyl-Dglucosamine, the monomeric subunit of chitin, and mediates binding of the bacterial cells to rabbit intestinal epithelial cells (44). Furthermore, it has been shown that Klebsiella pneumoniae is internalized efficiently by cultured human epithelial cells, presumably via an N-glycosylated receptor containing N-acetyl-glucosamine residues (13).…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive OMPs were shown to occur in Vibrio cholerae, 106 Aeromonas hydrophila, 107,108 Campylobacter jejuni, 109 Bartonella henselae, 110 Rickettsia rickettsii, 111 Salmonella typhimurium, 112 in enteroaggregative strains of Escherichia coli, 113 and in members of the Pasteurellaceae family. 114 By using the two-dimensional PAGE technique, De Mot and Vanderleyden 115 showed that a 33-kDa major outer membrane protein Critical Reviews in Microbiology Downloaded from informahealthcare.com by University of Memphis on 10/14/12…”
Section: Possible Involvement Of Outer Membrane Proteins (Omps) mentioning
confidence: 99%
“…In both cases, these MOMPs were proposed to play a role in attachment and colonization of plant roots by the producing bacteria. Adhesive OMPs (generally porins) occur in Vibrio cholerae (Sasmal et al, 1992), Aeromonas hydrophila (Quinn & Flower, 1995;Lee et al, 1997) and in an enteroaggregative strain of Escherichia coli (Debroy et al, 1995). Porins were shown to be involved in the invasion of epithelial cells by Salmonella typhimurium (Dorman et al, 1989) and Shigella flexneri (Bernardini et al, 1993).…”
Section: Involvement Of Omps In Aggregationmentioning
confidence: 99%